2022
DOI: 10.3390/vaccines10111798
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dexamethasone Treatment on COVID-19 Prognosis in Cancer Patients

Abstract: Background: Dexamethasone is used to treat cancer, relieve chemotherapy-induced nausea and vomiting, enhance cancer patients’ appetites, and treat COVID-19 patients. There is little evidence of the impact of a dexamethasone treatment plan on the severity of COVID-19 infections in cancer patients. This study explores whether dexamethasone treatment plan influences the severity of COVID-19 in dexamethasone-treated cancer patients. Methods: The medical records of 108 cancer patients receiving dexamethasone at Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Alternatively, switching the corticosteroid type to dexamethasone would be preferable, as the REMAP-CAP randomized study group [ 29 ] and the RECOVERY study group recommended [ 30 ]. This conclusion is similar to our previous study on COVID-19-infected cancer patients treated with dexamethasone, which found that it is preferable to continue the corticosteroid rather than stop it [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Alternatively, switching the corticosteroid type to dexamethasone would be preferable, as the REMAP-CAP randomized study group [ 29 ] and the RECOVERY study group recommended [ 30 ]. This conclusion is similar to our previous study on COVID-19-infected cancer patients treated with dexamethasone, which found that it is preferable to continue the corticosteroid rather than stop it [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…For this study, we analyzed data from the medical records of COVID-19-infected cancer patients at King Hussein Cancer Center (KHCC) who were between 18 and 91 years old. All KHCC patients were Middle Eastern (including Jordanians) and followed KHCC’s treatment protocols [ 27 ]. The KHCC Cancer Registry records were searched for PCR-positive COVID-19 patients (N = 1988).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations